Perforator Propeller Flaps for the Coverage of Middle and Distal Leg Soft-tissue Defects. Issue 5 (May 2018) - Mendieta, Mauricio; Cabrera, Rodrigo; Siu, Armando; Altamirano, Roderick; Gutierrez, Sandra
Abstract : Background: Local propeller flaps preserve the main vascular arteries of the lower extremity and muscle function, avoiding the need for a microsurgical anastomosis and the benefit of providing a "like with like" coverage. Our goal in this study was to demonstrate the versatility, safety, and complications of the local propeller flaps for lower extremity reconstruction. Methods: We present a series of 28 patients in whom we used local propeller flaps to restore small-to-medium soft-tissue defects of the lower limb in different hospitals of Managua, Nicaragua. Results: Flap average dimensions were of 48 cm 2 . Flap rotation was performed in 180 degrees in 85% of the cases. The propeller flaps were based on a single perforator, from the posterior tibial artery in 50%, anterior tibial artery in 39.3%, and peroneal artery in 10.7% of the cases. Complications occurred in 14% of the propeller flaps performed, with 3 partial necrosis of less than 15% of the flap transposed. Complications of the patients occurred in both sex groups; however, for the female group, there was a 75% of complications with a tendency toward statistical significance of P = 0.038. Donor site of the flap was closed primarily in 85.7% (24) of the cases. Conclusions: In our opinion, the availability and safety of local propeller flaps, justifies its use in cases where microsurgical techniques are not an option for the reconstruction of the middle and distal extremity, in small-to-medium defects of soft-tissue coverage of the lower limb.